George Craig of Galashiels : the life and work of a nineteenth century lawyer / John Finlay. - Finlay, John (Edinburgh scholarship online, 2020)
What was it like to practise as a lawyer and bank agent in a rural Scottish community on the cusp of modernity? George Craig was Sir Walter Scott's local banker, a writer, insurance agent, election agent and baron bailie of Galashiels. Based on thousands of recently discovered letters, this is the first study of a provincial nineteenth-century Scots lawyer and the community he served. Craig's many correspondents, from manufacturers, bankers, lawyers and law agents in London, Dublin, Jamaica and the US to weavers, tenant farmers and town clerks reflect Borders life in all its intensity and his letters paint a detailed picture of everyday existence. His story affords a fascinating glimpse of legal practice and estate management across the Borders, during a time of economic and political change, as Galashiels grew from a village into an important manufacturing centre.